2016
DOI: 10.1016/j.ijwd.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Hair camouflage: A comprehensive review

Abstract: Hair is venerated, cherished, and desired in societies throughout the world. Both women and men express their individual identities through their hairstyles. Healthy hair contributes to successful social assimilation, employment, and overall quality of life. Therefore, hair loss can have detrimental effects on almost every aspect of a person’s life. In this review, we discuss the myriad of options that aid in concealing and camouflaging hair loss to facilitate a healthier-appearing scalp. Camouflage options fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The fear of negative evaluation (in response to their changed identity; Goh, 2021 ) can decrease an individual’s self-esteem and perpetuate psychological distress ( Aldhouse et al, 2020 ; Davis & Callender, 2018 ; Saed et al, 2016 ). However, Black individuals may experience a “double stigma” ( Gary, 2005 ), relating to their ethnic origin and the negative connotations of mental health which may deter CED individuals from seeking support ( Grey et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fear of negative evaluation (in response to their changed identity; Goh, 2021 ) can decrease an individual’s self-esteem and perpetuate psychological distress ( Aldhouse et al, 2020 ; Davis & Callender, 2018 ; Saed et al, 2016 ). However, Black individuals may experience a “double stigma” ( Gary, 2005 ), relating to their ethnic origin and the negative connotations of mental health which may deter CED individuals from seeking support ( Grey et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In assessing how individuals cope with circumstances that challenge or threaten their body-image experiences, Cash et al (2005) identified three strategies: avoidance, appearance fixing, and positive rational acceptance. It has been reported that appearance fixing strategies or concealment in the form of wearing a wig that reflects the individual’s identity before hair loss may contribute to feelings of inauthenticity, thus creating psychological pressures ( Dinh & Sinclair, 2007 ; Aldhouse et al, 2020 ; Saed et al, 2016 ). Due to the complex and often unpredictable nature of alopecia, it has been reported that social support can play a significant role in the individual’s psychological wellbeing and emotional coping when dealing with hair loss ( Davey et al, 2019 ; Rafique & Hunt, 2015 ; Siedlecki et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Utilization of a hair prosthesis, that is, wigs can improve patient QOL; however, effective and reliable wigs are cost prohibitive and infrequently covered by medical insurance. 2 Herein we present the impact of wig hair prosthesis on a 70-year-old female patient with a history of biopsy-proven CCCA and androgenetic alopecia. This patient presented with a history of diffuse hair loss with areas of follicular dropout and scarring involving the crown of the scalp, vertex scalp, and parietal/frontal scalp (Fig.…”
Section: Dear Editorsmentioning
confidence: 99%
“…This form of cosmetic tattooing involves injection of pigment into the upper dermis to produce the impression of hair follicles on a scalp with decreased density. 38 SMP has been used for concealment of scarring alopecias, refractory alopecia areata, AGA, and scalp scars from previous trauma/surgery. 39 SMP is an individually-tailored procedure that takes into consideration several factors including needle size, penetration depth, and scalp resistance (ie, scarring).…”
Section: Camouflage Options For End-stage Hair Lossmentioning
confidence: 99%
“…Disadvantages to SMP and microblading include the need for multiple treatments, the risk of infection from needle exposure, and potential allergy to pigment dye. 38 , 42 Granulomatous reactions of the eyebrows have been reported in a small subset of patients who underwent microblading. 43 Patients should also consider the permanent nature of the dyes including the contrast that can arise as hair regrows or hair color changes with age.…”
Section: Camouflage Options For End-stage Hair Lossmentioning
confidence: 99%